2014
DOI: 10.1177/1363459314524803
|View full text |Cite
|
Sign up to set email alerts
|

International medical migration: A critical conceptual review of the global movements of doctors and nurses

Abstract: Background A critical appraisal of the discourse describing international medical migration around the turn of the 21 st century. Method A critical narrative review of a range of sources including grey literature, books, commentary and research reports, to trace the development and spread of specific causative models. English-language literature focussed on the Anglophone world. Findings The attribution of causative relations between the density of skilled medical workers (assumed to be linked with their migra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 58 publications
1
30
0
3
Order By: Relevance
“…Esse fato está inserido nas melhores condições que os países desenvolvidos podem oferecer (BRADBY, 2014), o que estimula países em desenvolvimento a estabelecer políticas de retenção de seus profissionais qualificados (AISA; CABEZA; LARRAMONA, 2014).…”
Section: Mobilidade: Interna E Externaunclassified
“…Esse fato está inserido nas melhores condições que os países desenvolvidos podem oferecer (BRADBY, 2014), o que estimula países em desenvolvimento a estabelecer políticas de retenção de seus profissionais qualificados (AISA; CABEZA; LARRAMONA, 2014).…”
Section: Mobilidade: Interna E Externaunclassified
“…In addition, receiving countries have also attempted to implement ethical recruitment policies, for example, by sending compensatory payments to countries that have trained a significant portion of the destination country's healthcare staff (Bradby, 2014). But these policy changes have largely been ineffective.…”
Section: Stemming the Medical Brain Drain: A Personal Perspective On mentioning
confidence: 99%
“…But even with all the discussion of policy and politics, a more fundamental point was emerging from our discussion-in order for developing countries to advance, they need to import ideas from the outside, because "alongside the amplification of migration is the mobility of capital, ideas and technology" (Bradby, 2014). And my mother firmly believes that volunteer efforts, born out of a sense of loyalty to the country of one's birth, will provide the vehicle for healthcare in Bangladesh to move forward, little by little.…”
Section: Stemming the Medical Brain Drain: A Personal Perspective On mentioning
confidence: 99%
See 1 more Smart Citation
“…An ethical perspective or lens, pointing to the need for an ethical response to the global inequities in health personnel distribution, was central to the WHO 2006 World Report 8,10 ; and is found in sociological analyses that suggest that recruitment and migration demonstrate that "the uneven global development of capital is at work. " 19 Aluttis et al, 6 discussing the consequences of market approaches, reported that there was an increase from approximately 40 to 270 companies engaged in international nurse recruitment in the United States between the late 1990s and mid-2000s. This and Zubaran's paper 9 contrast the ethical principle of autonomy -reflected in Article 3.4 of the Code: "Nothing in this Code should be interpreted as limiting the freedom of personnel … to migrate" 1 -with the principle of distributive justice (promoting equity) and social accountability.…”
Section: Analytical Lensesmentioning
confidence: 99%